1999
DOI: 10.1080/1369183x.1999.9976683
|View full text |Cite
|
Sign up to set email alerts
|

Puerto Ricans in the USA: A comparative approach

Abstract: This article discusses Puerto Rican migration within the broader context of Caribbean migration to the USA. The first part discusses the theoretical framework. The labour market incorporation of migrants is conceptualised as a result of the sociopolitical modes of incorporation which among other dimensions include the US foreign policy/geo-politics in the region; public opinion/perception of the migrants within the host society; the presence or absence of a migrant community as well as the class/racial composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…If the literature disaggregates the Latino pan-ethnic group, it often focuses on descriptive socioeconomic differences (Guarnaccia et al 2007). (Telles and Ortiz 2009;Portes and Rumbaut 2001;Aranda 2007;Grosfoguel 1999), contrasting them with the rapid upward economic integration of Colombians and Cubans (Aguilar 2009;Perez 1986;Grenier et al 2002). Existing research has also demonstrated that specific national groups, such as Mexicans and Puerto Ricans, are racialized more often than other Latino national groups (Alba et al 2014), which affects their identity formation and integration.…”
Section: Intra-latino Relationsmentioning
confidence: 99%
“…If the literature disaggregates the Latino pan-ethnic group, it often focuses on descriptive socioeconomic differences (Guarnaccia et al 2007). (Telles and Ortiz 2009;Portes and Rumbaut 2001;Aranda 2007;Grosfoguel 1999), contrasting them with the rapid upward economic integration of Colombians and Cubans (Aguilar 2009;Perez 1986;Grenier et al 2002). Existing research has also demonstrated that specific national groups, such as Mexicans and Puerto Ricans, are racialized more often than other Latino national groups (Alba et al 2014), which affects their identity formation and integration.…”
Section: Intra-latino Relationsmentioning
confidence: 99%
“…Unlike other immigrants, Puerto Ricans’ legal status allows them to move back and forth to and from the Island freely. This makes their political mode of incorporation distinct from that of other groups (Grosfoguel 1999). In spite of the fact that they do not cross international borders when they travel to the United States, Puerto Rico’s lack of sovereignty in combination with their collective sense of cultural nationhood (Duany 2002) means that they do cross geopolitical, social, racial, and cultural borders.…”
Section: Puerto Rican Migrationmentioning
confidence: 99%
“…Bryan worked for a U.S. company in sales, Robin was a successful attorney, and Franco had recently opened his own veterinary clinic. In all, Puerto Ricans' political mode of incorporation (Grosfoguel, 1999) facilitated social mobility among many participants in both mainland and Island samples. Those who did pursue their undergraduate degrees in Puerto Rico also were able to capitalize on Puerto Rico's relationship with the United States through professional labor recruiting practices.…”
Section: Citizenship-based Opportunities and Resourcesmentioning
confidence: 98%
“…Unlike other immigrants to the United States, Puerto Ricans' legal status allows them to freely move back and forth. This makes their political mode of incorporation distinct from that of other groups (Grosfoguel, 1999). aspects of their parents' home society culture with elements of the host society culture into bicultural, hybrid identities.…”
mentioning
confidence: 99%